Energy crisis, greenhouse gas emissions and sectoral growth reforms: repairing the fabricated mosaic - Qureshi, Muhammad Imran (Elsevier Ltd, 2016)
The study examined energy crisis and sought solutions for reforms in the largest regions of the world i.e. East Asia & Pacific, Europe and Central Asia, Latin America & the Caribbean, South Asia, and Sub Saharan Africa. The study used number of growth related factors over the period of 1975-2012. The results indicate significant relationship between electric power shortage and growth related specific factors; however, the intensity for each factor varies from region to region. The results of Granger causality verify multiple cause-effect channels in the different regions i.e. feedback hypothesis, economic factors driven electric shortage; electric shortage driven economic factors and no causal relationship between the variables. The results of variance decomposition analysis indicate that greenhouse gas emissions exhibit the largest contribution due to shortages in the electric power transmission. The study opens the debate for environmentalists, government and non-government officials to formulate the sustainable policies related to energy reforms.